Meeting the Challenges of Sepsis in Severe Coronavirus Disease 2019: A Call to Arms. (1st December 2022) - Walsh, Thomas J; Bright, Rick A; Ahuja, Aparna; McCarthy, Matthew W; Marfuggi, Richard A; Simpson, Steven Q
Abstract: Sepsis is a life-threatening organ dysfunction that is caused by a dysregulated host response to infection. Sepsis may be caused by bacterial, fungal, or viral pathogens. The clinical manifestations exhibited by patients with severe coronavirus disease 2019 (COVID-19)-related sepsis overlap with those exhibited by patients with sepsis from secondary bacterial or fungal infections and can include an altered mental status, dyspnea, reduced urine output, tachycardia, and hypotension. Critically ill patients hospitalized with severe acute respiratory syndrome coronavirus 2 infections have increased risk for secondary bacterial and fungal infections. The same risk factors that may predispose to sepsis and poor outcome from bloodstream infections (BSIs) converge in patients with severe COVID-19. Current diagnostic standards for distinguishing between (1) patients who are critically ill, septic, and have COVID-19 and (2) patients with sepsis from other causes leave healthcare providers with 2 suboptimal choices. The first choice is to empirically administer broad-spectrum, antimicrobial therapy for what may or may not be sepsis. Such treatment may not only be ineffective and inappropriate, but it also has the potential to cause harm. The development of better methods to identify and characterize antimicrobial susceptibility will guide more accurate therapeutic interventions and reduce the evolution of new antibiotic-resistant strains. The ideal diagnostic test should (1) be rapid and reliable, (2) have a lower limit of detection than blood culture, and (3) be able to detect a specific organism and drug sensitivity directly from a clinical specimen. Rapid direct detection of antimicrobial-resistant pathogens would allow targeted therapy and result in improved outcomes in patients with severe COVID-19 and sepsis.